Intencionalidade e consciência pura : a constituição do resíduo fenomenológico como acesso ao mundo na fenomenologia transcendental de Husserl - Juliana Torres Madureira (2017)
The purpose of this research is investigate the correlation between pure consciousness and the world of things in the phenomenology of Edmund Husserl, and understand from this correlation what is termed by him the phenomenological residue. At first, in Logical Investigations (1900/01), we try to delineate the conception of pure consciousness in view of intentionality. From this it was possible to delimit the phenomena of the intuitive experiences and the possibility of eidetic variation provided by the different degrees of intuition. Secondly, from The Idea of Phenomenology (1907) and Ideas I (Ideas for a Pure Phenomenology and for a Phenomenological Philosophy: General Introduction to Pure Phenomenology, 1913), we seek to understand the passage to phenomenological reductions and how they ensure a specific method for the reflexive analysis of pure consciousness. In distinguishing the phenomenological attitude from the natural attitude we try to elucidate the type of eidetic description that encompasses the horizon of the Umwelt (surrounding world) and the egological apparatus. Even in this second moment we circunscribe phenomenological temporality through the analysis of the flow of consciousness and show the summit of reductions in the foundation of transcendental phenomenology by Husserl. Next, we examine the structure of intentionality as the transcendental guide of constitutive analyzes. We find what leads to the constitutive basis revealed in the modes of bestowal and intentional unity, both contemplated by the noetic-noematic orientation. Finally, we explore the unfolding of Husserl's transcendental phenomenology through what remains in consciousness as a phenomenological residue and, as far as possible, we also indicate this theme present in later Husserl works. We have found that the focus on co-implication between phenomenological reductions and the transcendental constitution is indispensable to uncover the correlation between consciousness and the world of things. With this correlation we argue that the phenomenological residue does not result from the erasure of the world, but from a consciousness that is constituted with the world.